Usability of the Self‐Mini Nutritional Assessment® among Older Adults Receiving Home‐delivered Meals in Texas. (December 2015) - Moore, Britta Elizabeth; Friedman, BJ; Crixell, Sylvia Hurd
Abstract : Self‐screening tools for nutritional risk may be used to encourage older adults at risk of malnutrition to seek out preventive care. A recently available nutritional risk self‐screening tool, the Self‐Mini Nutritional Assessment ® (Self‐MNA ® ), had not been tested among diverse groups of older adults. The initial goal of this study was to compare results of the Self‐MNA ® to those of the Mini Nutritional Assessment ® ‐Short Form among a sample of homebound older adults who were newly enrolled in a Meals on Wheels program. Results suggest that the Self‐MNA ® screening tool was not practical for this sample, as evidenced by low rates of completion. Fewer than 80% completed the front of the form on the first attempt, and only 40% recorded a final screening score on the back of the form. The screening score is needed for successful utilization of the Self‐MNA ® . To increase usability of the Self‐MNA ® among older adults, it may be necessary to modify instructions and formatting to improve clarity.